2010
DOI: 10.1016/j.bbmt.2009.10.005
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary, Gonadal, and Central Nervous System Status after Bone Marrow Transplantation for Sickle Cell Disease

Abstract: We conducted a prospective, multicenter investigation of human-leukocyte antigen (HLA) identical sibling bone marrow transplantation (BMT) in children with severe sickle cell disease (SCD) between 1991 and 2000. To determine if children were protected from complications of SCD after successful BMT, we extended our initial study of BMT for SCD to conduct assessments of the central nervous system (CNS) and of pulmonary function 2 or more years after transplantation. In addition, the impact on gonadal function wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
148
3
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 174 publications
(160 citation statements)
references
References 36 publications
7
148
3
2
Order By: Relevance
“…3,33 In a series studying 137 patients on chronic transfusion therapy for secondary stroke prevention, 31 patients had a second stroke while receiving chronic transfusion therapy. 33 Similar to the results described by Walters et al, 11 our series also showed a stabilizing effect on central nervous system function and prevention of future stroke. However, neurological toxicities due to calcineurin inhibitors can occur following allo-SCT 34,35 as noted in one patient.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…3,33 In a series studying 137 patients on chronic transfusion therapy for secondary stroke prevention, 31 patients had a second stroke while receiving chronic transfusion therapy. 33 Similar to the results described by Walters et al, 11 our series also showed a stabilizing effect on central nervous system function and prevention of future stroke. However, neurological toxicities due to calcineurin inhibitors can occur following allo-SCT 34,35 as noted in one patient.…”
Section: Discussionsupporting
confidence: 78%
“…With respect to pulmonary function, stability and improvement were observed at 2 years post allo-SCT, similar to the results that have been reported by Walters et al 11 following BU/CY conditioning and sibling BMT in pediatric recipients with SCD. Furthermore, stability in the pulmonary function tests post allo-SCT also suggests that our conditioning regimen did not induce significant long-term pulmonary toxicity post allo-SCT.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Among evaluable male patients, four out of 13 patients tested had abnormal luteinizing hormone and folliclestimulating hormone levels and 10 out of 13 had abnormal testosterone levels; whereas eight of 14 females tested had either abnormal luteinizing hormone, follicle-stimulating hormone or estradiol levels and 75% had amenorrhea. 19 As gonadal toxicity may be correlated with the pubertal stage at the time of transplant, long-term follow-up of our young patients will be necessary to assess the ultimate gonadal function post transplant. Of interest, infertility was not a major concern for the eligible families we encountered.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, recent evidence from Walters et al strongly suggests that, when available, matched-sibling donor HSCT should be the first option for the secondary prevention of strokes. 28 In the most comprehensive study to date, which was performed from 1991-2000, none of the 28 patients with engraftment experienced recurrent strokes or had evidence of silent cerebral infarct events after HSCT, with a mean follow-up of 3.6 years (range 0.6-7.3 years).…”
Section: Hsctmentioning
confidence: 99%